Листи Г. Залюбовського до Я. Новицького (до 170-річчя від дня народження Г. Залюбовського) - Іваннікова, Л.; Мицик, Ю. (Народна творчість та етнографія, 2006)
This article was written to 170th Anniversary- of H. Zalyubovsky (1836—1898). He was a famous Ukrainian folklorist, ethnographer, writer, who considered folklore to be a good historical source. He was recording folklore in Kharkiv and Katerinoslavski regions, was published in folklore editions and participated in linguistic groups. He passed to Borys Hrinchenko more then 2000 words for the “Dictionary of die Ukrainian Language” . He also was very active in public life. The authors of the article added nine new (not published before) letters to his biography written by H. Zalyubovsky to Y. Novytsky (1847—1925). These letters have some interesting information about the history- of the Zaporizhya region and the history of Ukrainians in 19th century in general.